CORRELATION OF MATERIAL GRADATION COEFFICIENT WITH DENSITY AND SOIL SHEAR STRENGTH - Herman Wahyudi; Kukuh Prihatin (Journal of Civil Engineering, 2011)
Reclamation fill requires material to fulfil the particle gradation requirements as follow : gravel 30% max, sand 50% min, and silt-clay 20% max. Generally, field officer wants to know the density degree of material when it has arrived in the field immediately and easily by using sieve testing. Water content changing caused by rainy season and tidal, taking the largest part of affecting the density and strength of soil. This laboratory test research is using material taken from quarry river, shores and hills which have requirement as follows: silt-clay 20% max, sand 80% min, and gravel which has represented by sand. This material is tested using sieve and hydrometer to determine Cu (coefficient of uniformity) and Cc (coefficient of curvature). Next step is to dense using Modified Proctor and Direct Shear testing with saturated water value (on Zero Air Void line) and non-saturated (on wopt). Research result shows the bigger the Cc/Cu value is (soil is more homogen), maximum dry density will become smaller, dmax (dmax = -0,808.Cc/Cu + 2,061) and also the optimal water content will become bigger, wopt (wopt = 7,512.Cc/Cu + 9,492). The bigger the Cc/Cu, cohesion effectiveness value(C’) and effective internal angle friction ') will become smaller. Non-saturared condition is showing bigger value ( C’ = -0,088.Cc/Cu + 0,087 and ' = - 29,886.Cc/Cu + 53,309) than in saturated condition ( C’ = -0,057.Cc/Cu + 0,072 and ' = -33,052.Cc/Cu + 48,761) for the same Cc/Cu value. Similarity between these parameters is only valid if reclamation fill material composition used are as follow: sand 80% min, silt-clay 20% ax, and Cu limit of 1≤Cu≤50.